A Rare Case Report on Jaundice, Alcoholic Liver Disease with a History of Herbal Medicine Induced Liver Injury - G, Varsha (Journal of Biomedical and Pharmaceutical Research, 2024)
Background: Alcoholic liver disease (ALD) is a complex condition caused by excessive alcohol consumption, affecting fatty liver, alcoholic hepatitis, and cirrhosis. Risk factors include alcohol intake, genetic predisposition, and co-existing liver conditions. Alcoholic fatty liver disease (AFLD) accumulates excessive fat in the liver, leading to steatosis and fibrosis. ALD complications include portal hypertension, liver failure, and hepatocellular carcinoma. The use of herbal medicines, such as tamarind and neem extracts, is also concerning due to potential liver damage. Increased awareness and caution are needed from patients and healthcare providers. Case report: A 33-year-old male patient presented with symptoms including right hypochondrium pain, yellowish discoloration of the sclera, fever, decreased urine output, light yellow tongue, and generalized weakness. He was a chronic alcoholic, consuming various alcoholic beverages for 15 years. His dietary routine was mixed, but he preferred non-vegetarian foods. His family suggested he consume traditional herbal medicine to treat jaundice. After collecting his history, lab tests were conducted to confirm his diagnosis of alcoholic liver disease (ALD) with herbal medicine-induced liver (DILI). LFT tests were alarming, and he was diagnosed with alcoholic liver disease with jaundice and DILI due to herbal medicine. To improve his symptoms and prevent liver failure complications, he was prescribed a list of medications to improve his symptoms and to prevent complications of liver failure. Discussion: A holistic treatment approach is needed for patients with alcoholic liver disease and herbal medicine-induced liver injury, focusing on symptom relief, liver function enhancement, and complication prevention. This includes lifestyle changes, nutritional support, and managing potential issues. Regular monitoring is crucial for adjustments. Conclusion: This case report highlights the complex relationship between alcoholic liver disease and herbal medicine-induced liver injury, especially in jaundice cases. It emphasizes the need for thorough patient histories, increased awareness of hepatotoxic potential, and educating patients about alcohol and herbal supplement risks. It calls for multidisciplinary collaboration, enhanced regulation, and safety evaluations of herbal medicines to protect public health. It also underscores the importance of continuous monitoring and monitoring patients with liver injury histories.Keywords: ALD, Herbal medicine, DILI, Liver failure, Patient care